Terahertz, Ultrafast Lasers and Their Medical and Industrial Applications - Wadi Harun, Sulaiman (IntechOpen, 2022)
Laser materials processing has made tremendous progress and is now at the forefront of medical and industrial applications. The book describes recent advances in terahertz and ultrafast laser applications. Chapter address such topics as terahertz quantum cascade lasers, femtosecond lasers in ophthalmology, laser surface texturing, and laser ablation.